Conjunctival biopsy in adult form galactosialidosis. Issue 3 (March 1993) - Usui, T; Sawaguchi, S; Abe, H; Iwata, K; Oyanagi, K
Abstract : Conjunctival biopsy was performed in two siblings with adult-form galactosialidosis. Electron microscopically, several types of intracytoplasmic inclusion were observed in the fibroblasts in conjunctival stroma, lymphatic capillary endothelial cells, Schwann cells, and epithelial cells. Membrane-bound vesicles with fibrillogranular content were frequently observed, and occasional lamellar structures were noted in these inclusions. Dense granular inclusions and oil droplets were also seen. Dense granular inclusions have not been reported in this disease previously.